Biomass Production a Stronger Driver of Cellulosic Ethanol Yield than Biomass Quality. (1st September 2017) - Sanford, Gregg R.; Oates, Lawrence G.; Roley, Sarah S.; Duncan, David S.; Jackson, Randall D.; Robertson, G. Philip; Thelen, Kurt D.
Abstract : Core Ideas: Fermentable sugars were greatest in corn stover > perennial grasses > polycultures. Corn stover had the highest ethanol content. Miscanthus had the highest ethanol yield potential on a per hectare basis. Ethanol yield potential per hectare of switchgrass ≥ corn stover. Biomass yield was the strongest driver of per hectare ethanol yield. Many crops have been proposed as feedstocks for the emerging cellulosic ethanol industry, but information is lacking about the relative importance of feedstock production and quality. We compared yield and sugar content for seven bioenergy cropping systems in south‐central Wisconsin (ARL) and southwestern Michigan (KBS) during three growing seasons (2012 through 2014). The cropping systems were (i) continuous corn stover ( Zea mays L.), (ii) switchgrass ( Panicum virgatum L.), (iii) giant miscanthus ( Miscanthus × giganteus Greef & Deuter ex Hodkinson & Renvoize), (iv) hybrid poplar ( Populus nigra × P. maximowiczii A. Henry 'NM6'), (v) native grass mix, (vi) early successional community, and (vii) restored prairie. A high‐throughput pretreatment and fermentation assay showed corn stover with the highest sugar content (213 g glucose kg −1 [Glc] and 115 g xylose kg −1 [Xyl]) followed by the two monoculture perennial grass treatments (154 [Glc] and 88 [Xyl]) and then the herbaceous polycultures (135 [Glc] and 77 [Xyl]). Biomass production and sugar content were combined to calculate ethanol yields. Miscanthus had the highest per hectare ethanol yields (1957 l ha −1 yr −1 ARL, 2485 l ha −1 yr −1 KBS) followed by switchgrass (1091 l ha −1 yr −1 ARL, 1017 l ha −1 yr −1 KBS) and corn stover (1121 l ha −1 yr −1 ARL, 878 l ha −1 yr −1 KBS). Perennial grass cropping systems (i.e., switchgrass and miscanthus) had higher per hectare ethanol yields at both sites relative to diverse systems that included dicots. Despite feedstock differences in fermentable sugars, biomass production was the strongest driver of per hectare ethanol yield.